Two new species of Hypancistrus (Siluriformes: Loricariidae) from the rio Xingu, Amazon, Brazil - Leandro Melo de Sousa; Erilda Barbosa de Sousa; Renildo de Oliveira Ribeiro; Mark H. Sabaj; Jansen Zuanon; Lúcia Rapp Py-Daniel (Neotropical Ichthyology)
Abstract Hypancistrus was proposed as a monotypic genus for a highly unique species, H. zebra, known only from a short stretch of the Middle rio Xingu on the Brazilian Shield. Subsequent studies added eight species, all described from river systems draining the Guiana Shield. Analysis of Hypancistrus specimens from the middle and lower Xingu detected two new species that can be separated from its congeners based on color pattern and body size of adults, and that are well known from the ornamental fish trade. Due to their non-overlapping distributions, the prospects of conserving the two species are quite different. One of the species is relatively safe due to its relatively large distribution throughout the Lower Xingu channel up to the downstream end of Volta Grande do Xingu, while the other is in need of urgent protection because it is restricted to a short stretch of the Middle Xingu channel at depths greater than 15 meters, and its distribution lies entirely within the impact zone of the Belo Monte Hydroelectric Power Plant Complex.